Reducing the time delay of oxygen transport to the neonate on continuous positive airway pressure support: A bench study - Tejkl, Leos; Kudrna, Petr; Rafl, Jakub; Bachman, Thomas E. (Frontiers in Pediatrics, 2023)
Background: Premature newborns often require oxygen support as part of their therapy. Systems for oxygen administration are developed to assure adequate oxygenation of newborns. Several factors were identified in the systems that contribute to the time delay between the change in the set inspiratory oxygen fraction and its actual delivery to tissues. In this study, we aimed to reduce the physical delay in oxygen delivery to newborns. Methods: We developed an O2 Flush System (O2-FS) that brings the source of oxygen as close to a patient as possible to make oxygen available for rapid delivery that compensates for the physical delay in the ventilator circuit. The O2-FS system is built around an electromechanical on/off valve. We validated the O2-FS concept in experiments with non-invasive Continuous Positive Airways Pressure (CPAP) ventilators. Results: The O2-FS accelerated oxygen delivery with all the tested systems and arrangements, typically by 5–15 s. We also observed that the application of supplemental oxygen increased the pressure in the ventilator circuit by 3–4 cmH2O which may mitigate the apneic pauses that are common in premature newborns. Conclusions: The O2-FS system may work as a universal accessory of the CPAP lung ventilator and shorten the distribution of oxygen to the patient during oxygen desaturation events, possibly eliminating or interrupting apneic pauses is in neonates, for whom oxygen therapy is an essential treatment. In clinical practice, the O2-FS could help maintain normoxemic saturation values through adequate oxygen dosing in preterm neonates, thus reducing morbidity and mortality.